Socio-environmental Conflicts and Local Incidence: The Conflict Over El Mauro Tailings Dam in Choapa - Cuevas Gutiérrez, Camila (Estado, Gobierno y Gestión Pública, 2024)
This article analyzes the impact of socio-environmental conflicts in Chile through a case study focused on the dispute over the El Mauro tailings dam in the Province of Choapa between 2001 and 2016. The objective was to investigate the elements that explain why the conflict manages to influence territorial development management despite not achieving the central demand of its opponents: the cessation of the tailings dam operation. Based on a process tracing method, which included document analysis and qualitative interviews with residents and experts on the case, it was identified that the capacity to engage with specialized actors and the entry into the judicial arena are the elements that explain the conflict’s ability to impact the territory.